Influence of religiosity on medical students’ mental health - Leite,Larissa Cruvinel (2021)
Abstract: Introduction: Mental health was included as one of the top ten health indicators and studies have shown it is related to religiosity and spirituality (R/S). Objective: The aim of the present study is to evaluate whether the degree of R/S of medical students influences anxiety and depression disorders during undergraduate school. Method: This study was carried out with a convenience non-probabilistic sample, consisting of 298 students. The Duke Religiosity Index in Brazilian Portuguese (P-DUREL) was used in questionnaire form, whereas, to map depression, anxiety and stress, DASS-21 was applied. Results: It was demonstrated that the different dimensions of religiosity have no association with the students’ emotional disorders, anxiety and stress. Conclusions: It is possible to propose recommendations for future research, so that the results can be used in meta-analysis studies. Studies that did not show a significant association between the variables cannot be neglected, so that the positive and negative dimensions of the association between R/S and mental health can be investigated.